The non-observance of grice’s maxims in Sasak - Lalu Nurul Yaqin,; Thilagavathi Shanmuganathan, (Penerbit Universiti Kebangsaan Malaysia, 2018)
This study investigates how the Sasak people of Lombok Indonesia interact among each other in naturallyoccurring interactions. The Politeness theory stipulates that the language of communication associates social reality and language use in real communities. Grice’s theory is based on the assumption that people are cooperative in communication. It follows that the notions of politeness are likely to exhibit this observance of being cooperative. However, studies have shown that the Cooperative Principle and the attendant maxims are almost never strictly followed in daily conversations and so, what prompts this non-observation? The Sasak people are known to be naturally shy and communicate with each other using the Nggeto-Nggete dialect. Twenty participants were randomly selected from a population in East Sukamulia, a place where Sasak is spoken. Based on the data collected from informal domestic settings such as exchanges in the shop and home, and between the family and neighbourhood, the extent to which the Cooperative Principle and maxims are observed and the politeness strategies used to perform the exchanges are established. The findings reveal that the Sasak speakers of the Nggeto-Nggete dialect did not observe Grice's maxims and its principles when communicating with each other. They do so in order that they communicate information clearly to each other while observing what they regard to be moral etiquette and standard of decorum.